Experiment of bukit bunuh handaxes manufacturing technology - Bakry, Noridayu; Abdullah, Jeffrey (School of Social Sciences, 2015)
The Bukit Bunuh site is one of the Palaeolithic site in Lenggong Valley in the meteorite impact area, which is located 10km from Lenggong town, in the hulu Perak district. This site discovered a handaxe tools which is the important findings that will change the “Movius Line” theory that reflects the different levels of technology between Southeast Asia and the West. The experimental of manufacturing technology is conducted to reconstruct the techniques used by ancient people at Bukit Bunuh site to produce these tools. The experimental result proved that Bukit Bunuh handaxes also